2001
DOI: 10.1046/j.1360-0443.2001.9634458.x
|View full text |Cite
|
Sign up to set email alerts
|

Social dimensions of adolescent substance use

Abstract: The models and relationships presented in this paper show that a constellation of behaviours are related to adolescent substance use. Also demonstrated is that behaviours cannot be considered in isolation, but need to be examined from an holistic or biopsychosocial standpoint. These relationships are complex and future research should consider not only causality of adolescent substance use, but also of the aetiology of the satellite behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
85
2
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 22 publications
12
85
2
6
Order By: Relevance
“…Although not the primary focus of this study, the predictive effects of early substance use are evident; particularly, the increased risks associated with early use of double (6-to 8-fold) and triple (12-to 15-fold) combinations of alcohol, tobacco and marijuana for progression to more frequent use, in agreement with other studies (Best et al, 2000;Sutherland & Shepherd, 2001). Further, early combined alcohol plus tobacco use shows a gateway effect in predicting later marijuana use; conversely, however, early tobacco plus marijuana use is not associated with later alcohol use.…”
Section: Tablesupporting
confidence: 77%
See 1 more Smart Citation
“…Although not the primary focus of this study, the predictive effects of early substance use are evident; particularly, the increased risks associated with early use of double (6-to 8-fold) and triple (12-to 15-fold) combinations of alcohol, tobacco and marijuana for progression to more frequent use, in agreement with other studies (Best et al, 2000;Sutherland & Shepherd, 2001). Further, early combined alcohol plus tobacco use shows a gateway effect in predicting later marijuana use; conversely, however, early tobacco plus marijuana use is not associated with later alcohol use.…”
Section: Tablesupporting
confidence: 77%
“…Further, Kumpulainen and Roine (2002) found that early (age 12) perception of school failure and low selfesteem in girls, and interpersonal problems and aggressive tendencies in boys, were more important predictors of heavy alcohol use at age 15 than early depressive symptomatology. Sutherland and Shepherd (2001) found strong relationships between social factors and substance use outcomes in 11-16 year olds (n = 4516), with perceived academic performance ranking third in importance after 'concurrent second or third substance use', and 'having been in trouble with police' as predictors of substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences in the methods of diversion may explain the results in our and other studies (Buurma et al, 2008). The socioeconomically disadvantaged are well known as a risk group of substance use disorders (Lee et al, 2013;Sutherland and Shepherd, 2001) but our results may be influenced by their higher disease prevalence and by socioeconomic differences in drug prescription rates. Overall, the majority of drivers had a low educational level, a low level of income and were living alone.…”
Section: Main Findings and Their Interpretationcontrasting
confidence: 45%
“…Carr, 2000) show that use of psychoactive substances among adolescents in school is of particular concern because it may have a negative long term cognitive effect on the youngsters who use the substances. Further researches also suggest a negative association between adolescents' school performance and substance use, and premise that students who use psychoactive substances are at a greater risk of performing poorly in school and vice versa (Bergen et al, 2005;Diego, Field, & Sanders, 2003;Ellickson et al, 2001;Sutherland & Shepherd, 2001). …”
Section: Discussionmentioning
confidence: 99%